Which psychological characteristics strengthen “The entrepreneurial intention-action relationship”?: An extension of the theory of planned behavior - Denny Bernardus; Fulgentius Danardana Murwani; Elia Ardyan; Liestya Padmawidjaja; Imanuel Deny Krisna Aji; Stefan Yudana Jatiperwira; Djoko Dwi Kusumojanto; Cipto Wardoyo; Yustinus Budi Hermanto (Cogent Business & Management, 2020)
This study extends the literature of the theory of planned behavior in the context of entrepreneurship. Specifically, this study is intended to verify which psychological characteristics moderate the relationship between entrepreneurial intention and entrepreneurial action. Internal locus of control, innovativeness, and performance goal orientation are proposed to moderate "the entrepreneurial intention-action relationship", because those variables have the likelihood for individuals to take action to start a new business. Adopting a cross-sectional design, the data were collected from 188 undergraduate students who participated in an entrepreneurship project and analyzed using hierarchical regression analysis. The results demonstrated that internal locus of control was found to strengthen "the entrepreneurial intention-action relationship", whereas innovativeness and performance goal orientation did not moderate that relationship. The findings provide practical implications not only for entrepreneurs to consider internal locus of control and entrepreneurial intention in starting a business, but also for entrepreneurship educators in developing a start-up business curriculum based on students' psychological characteristics.
Keywords: 650; entrepreneurial intention-action link; internal locus of control; innovativeness; performance goal orientation